The lived experience of older adults'occupational adaptation following a stroke - Williams, Shoshannah; Murray, Carolyn (© 2013 Australian Occupational Therapy Journal, 2017)
This article was published in the Australian Occupational Therapy Journal [© 2012 Occupational Therapy Australia] and the definite version is available at: http://onlinelibrary.wiley.com/doi/10.1111/1440-1630.12004/full